1989
DOI: 10.1007/bf00156706
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in the definition of ?stereoscotoma? using temporal detection of thresholds of dynamic random dot stereograms

Abstract: Temporal detection thresholds are reported from two subjects to dynamic random dot stereograms (DRDSs) of both crossed and uncrossed disparity. The stimuli were 1 degree square, of 0.25 degrees disparity and were presented at 81 positions in a 9 degree square central region. In both subjects crossed disparity stimuli were detected at shorter durations. One subject displayed particularly acute stereoscopic vision and presented a pattern of temporal thresholds increasing gradually with eccentricity. The other su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Ample psychophysical evidence indicates perceptual asymmetry between crossed and uncrossed disparity conditions. Crossed disparity requires less stimulus duration than uncrossed disparity for stereoscopic depth perception (Finlay et al 1989;Landers and Cormack 1997;Manning et al 1987;Patterson et al 1995;Tam and Stelmach 1998). Therefore for a given stimulus duration, stereo threshold is lower for crossed than uncrossed disparity.…”
Section: The Validity Of the Neuron-orthoneuron Hypothesis In V4 For mentioning
confidence: 99%
See 1 more Smart Citation
“…Ample psychophysical evidence indicates perceptual asymmetry between crossed and uncrossed disparity conditions. Crossed disparity requires less stimulus duration than uncrossed disparity for stereoscopic depth perception (Finlay et al 1989;Landers and Cormack 1997;Manning et al 1987;Patterson et al 1995;Tam and Stelmach 1998). Therefore for a given stimulus duration, stereo threshold is lower for crossed than uncrossed disparity.…”
Section: The Validity Of the Neuron-orthoneuron Hypothesis In V4 For mentioning
confidence: 99%
“…This section formulates the responses of the disparity energy model proposed by Ohzawa et al (1990). Many of the mathematical details have been previously described for other stimuli such as sinusoidal gratings (Fleet et al 1996;Qian 1994;Qian and Zhu 1997;Zhu andQian 1996), static RDSs (Fleet et al 1996;Qian 1994;Qian and Zhu 1997;Zhu andQian 1996), dynamic RDSs (Prince et al 2002a), SFSs containing a thin static bar (Mikaelian and Qian 2000; Qian 1994), and SFSs containing a thin sweeping bar (Anzai et al 1999;Ohzawa et al 1997). Here, we derive the analytical solution for the disparity tuning of a model complex cell, in response to a dynamic RDS and a thin static bar SFS.…”
Section: A P P E N D I Xmentioning
confidence: 99%
“…At the very least, one needs different spatiotemporal characteristics for stereo processing over crossed and uncrossed ranges of disparity, which again leads to the more parsimonious conclusion that there are at least two separate mechanisms. Indeed, the spatiotemporal characteristics of these depth^disparity mechanisms have been estimated and are found different (Finlay et al 1989;Patterson et al 1995;Richards 1972;Schor and Wood 1983).…”
Section: Relation Between Planar and Volumetric Testsmentioning
confidence: 99%
“…Multiple psychophysical studies ( Birch, Gwiazda, & Held, 1982 ; Breitmeyer, Julesz, & Kropfl, 1975 ; Finlay, Manning, Dunlop, & Dewis, 1989 ; Herring & Bechtoldt, 1981 ; Manning, Finlay, Neill, & Frost, 1987 ; Patterson et al., 1995 ; Regan, Erkelens & Collewijn, 1986 ; Schor & Wood, 1983 ) have reported on asymmetries in sensitivity for far and near disparities (see also reviews in Landers & Cormack, 1997 ; Mustillo, 1985 ; Regan, Frisby, Poggio, Schor, & Tyler, 1990 ). For example, developmental work showed that infants develop near stereopsis prior to far stereopsis ( Birch et al., 1982 ).…”
Section: Psychophysicsmentioning
confidence: 99%
“…For example, developmental work showed that infants develop near stereopsis prior to far stereopsis (Birch et al, 1982). In the adult, it has been reported that there are different spatiotemporal response functions for far and near disparities (Finlay et al, 1989;Manning et al, 1987;Patterson et al, 1995;Schor & Wood, 1983).…”
Section: Psychophysicsmentioning
confidence: 99%